Greatness engendered : George Eliot and Virginia Woolf - Booth, Alison (Reading women writing., 1992)
In this forceful and compelling book, Alison Booth traces through the novels, essays, and other writings of George Eliot and Virginia Woolf radically conflicting attitudes on the part of each toward the possibility of feminine greatness.